Evaluation of a rotating drum mixer - Stark, C.R.; Fahrenholz, C.H.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A "rotating drum" type mixer was tested to determine if it could produce a uniformly mixed feed. Feed was manufactured in four separate trials, which examined addition sequence, mixing time, mixer capacity, and liquid addition. Uniformly mixed feed was obtained after 8 min, when ingredients were properly sequenced and mixed. Smaller batch sizes decreased the time required to obtain a uniform mixture. The mixer distributed liquid uniformly through the feed and had excellent clean-out capabilities.
Keywords: Swine; Rotating drum mixer; Feed uniformity; Feed manufacturing; Mixer testing